Optimization of culture conditions for mycelial growth of the wild edible mushroom Phlebopus portentosus PPBR01 - Boonrung, Santhaya; Kanjak, Teerayut; Sombatwong, Junjira; Vichuma, Pornpimon; Salee, Nuchjaree (Asian Health, Science and Technology Reports, 2023)
The objective of the present study was to optimize the optimal media and culture conditions for the mycelial growth of the wild edible mushroom, Phlebopus portentosus PPBR01 on agar medium. The mycelium of the strain was isolated from the fruiting bodies and cultured on commercial potato dextrose agar (commercial PDA) medium. To optimize the culture conditions for the mycelium growth rates of the mushrooms, various solid media, carbon and nitrogen sources, temperatures and initial pH were determined with single-factor experiments. Five local crops consisting of potato, pumpkin, taro, corn and cassava were used as the nutrient source in agar media while commercial PDA was used as the control. Among the six culture media tested, potato agar and pumpkin agar were the best for mycelia growth. Starch was the best carbon source and (NH4)2SO4 was the best nitrogen source for promoting fungal growth in terms of mycelial density. The mushrooms were found to grow best at temperatures ranging from 29-30°C. In addition, the mushroom was able to grow at a pH ranging from 5-9, with an optimal pH of 5. The present findings provide valuable information concerning optimal growth conditions for the in vitro culture of P. portentosus.